Model Pembelajaran Two Stay Two Stray (TSTS) Terhadap Kemampuan Komunikasi Matematis - Alisa, Nur; Susanti, Dwi; Hermansyah; Widyawati, Eka (FKIP Universitas Mataram, 2025)
Mathematical communication skill (KKM) is the ability of students to communicate ideas in writing to solve problems. However, students still have not been able to solve the problem and do not write conclusions. So it is necessary to apply the Two Stay Two Stray (TSTS) learning model with a realistic approach to student KKM. The TSTS learning model can give students freedom to understand the material, develop mathematical ideas, write, and convey the results of their thinking to other students. This research was an experimental research with a posttest-only nonequivalent groups design. Sampling was conducted using the purposive sampling technique based on consideration of the lowest class average score, and a population equality test was performed using a one-way ANOVA test. Data collection was carried out using a posttest containing 4 questions and analyzed using descriptive statistics and a one-way ANOVA test. The results showed that the value of Fcount: 6.629159 > Ftable: 4.003983, so that the learning model affects math communication skill. Furthermore, a double comparison test was conducted with the Scheffe method and obtained that Fcount: 6.5863 > Ftable: 4.003983, which shows a significant difference between the average of the TSTS learning model with a realistic approach and the conventional learning model. So, it is concluded that the TSTS learning model with a realist approach is the best.